Two-fold sustainability - Adobe with sawdust as partial sand replacement - Jokhio, Gul A.; Sharifah Maszura, Syed Mohsin; Gul, Yasmeen (IOP Publishing Ltd, 2018)
Adobe is a material that is economic, environment friendly, and provides better indoor air quality. The material required for the preparation of adobe include clay, sand, and sometimes straw or other organic materials. These materials do not require industrial processing or transportation, however, sand mining has been recently posing a threat to the environment. Therefore, to enhance the existing sustainability of adobe, sand can be partially or fully replaced by other waste materials. This approach will not only solve the problem of excessive sand mining, it will also address the issue of waste management. Sawdust is one such waste material that can be used to partially replace sand in Adobe. This paper presents the results of compressive and flexural test carried out on Adobe samples with partial sand replacement by sawdust. The results show that about 4% sand replacement by volume produces higher compressive strength, whereas the flexural strength reduces with the use of sawdust. However, since flexural strength is not a critical property for adobe, it is concluded that replacing sand with sawdust by about 4% of volume will be beneficial.